Ocular in situ gel: An overview - Majeed, Asmat; Khan, Nisar Ahmad (Journal of Drug Delivery and Therapeutics, 2019)
Eye is the most sensitive organ of the body. Designing of ocular drug delivery system is the most challenging field for pharmaceutical scientists as less than 5% of administered drug enters the eye due to the complicated anatomical structure of the eye, small absorptive surface and low transparency of the cornea, lipophilicity of corneal epithelium, pre corneal loss (due to nasolacrimal drainage), bonding of the drug with proteins contained in tear fluid, blinking, low capacity of conjunctival sac, that restricts the entry of drug molecule at the site of action and ultimately leads to poor ocular therapy. To improve ophthalmic drug bioavailability, there are considerable efforts directed towards newer drug delivery systems for ophthalmic administration. These novel drug delivery systems offer manifold advantages over conventional systems as they increase the efficiency of drug delivery by improving the release profile and also reduce drug toxicity. A lot of research going on in this area proves the fact that in situ gelling systems can be beneficial in the ocular drug delivery. In situ gel forming systems are drug delivery systems that are in solution form before administration in the body but once administered, undergo in situ gelation, to form a gel triggered by external stimulus such as temperature, pH etc. This review is to Specify a brief summary about in situ gels, various approaches for in situ gelling systems, different types of polymers used in in situ gels, their mechanisms of gel formation and evaluation of polymeric in situ gel. Keywords: in situ gel, polymers, Temperature induced in situ gel system, pH induced in situ gel system, Ion activated systems.